Review of International Law (Lex Specialis) on the Problems of the South China Sea (SSS) Boundary Conflict and the View of Indonesia's Diplomacy - Yohanes Firmansyah; Yana Sylvana; Hanna Wijaya; Michelle Angelika S (International Journal of Social Science and Religion (IJSSR), 2021)
The South China Sea (SCS) is a geographical area that is rich in natural resources such as crude oil and is a very strategic area of ​​the economy. The SCS is surrounded by several littoral states which cause conflicts between coastal countries over the right to power over South China. There are at least 9 countries conflicting with each other in the SCS, such as the People's Republic of China (PRC), Taiwan, Malaysia, Vietnam, the Philippines, Brunei Darussalam, Burma and Indonesia. The problem became even more serious when the Declaration of Decision of the International Court of Justice or the Permanent Court of Arbitration (PCA) as the highest international institution was opposed by China because it was considered detrimental and weakening China's power. This research aims to specifically discuss the geographical position of the SCS and international law (especially UNCLOS), diplomacy issues in the maritime sector, how to regulate sea areas according to international law and disputes that occur in the SCS and the role of Indonesian diplomacy in responding to the decision of the Permanent Court of Arbitration (PCA)